Retraso en el diagnóstico de un cuadro grave de enfermedad de Huntington juvenil: caso clínico (2014)
Huntington's disease is a neurodegenerative disease that is clinically manifested as mood and personality changes, loss of cognitive functions and choreiform movements. The pattern of inheritance is autosomic dominant. It is due to the gradual expansion of a cytosine, adenine, guanine trinucleotide in a gene that codifies the protein Huntington. The molecular diagnosis must be performed to confirm the diagnosis. Genetic counseling must be carefully done due to the high suicide risk among these patients. We present the case of a fourteen-year-old male with a severe disease, poor social support and an unclear pattern of inheritance.